Retracted: Diversities of mosquito species of different locations in Dhaka city (Progressive Agriculture, 2018)
Retraction NoticeOn 23th October 2025 the Editorial Board of the journal Progressive Agriculture agreed to retract the article ‘Diversities of mosquito species of different locations in Dhaka city’ published in Progressive Agriculture, Vol. 28(4) pages 295-301 (DOI: https://doi.org/10.3329/pa.v28i4.36369) as it was found to be a duplicate publication of the following published article: ‘Surveillance of mosquitoes in some selected parks and gardens of Dhaka city, Bangladesh’ by Kabirul Bashar, Faria Farhana Rain, Mahmuda Jesmin, Asaduzzaman published in International Journal of Mosquito Research 2014, Vol.1(2) pages 5-9 https://www.dipterajournal.com/pdf/2014/vol1issue2/PartA/6.1-654.pdf. This error is regretted.